2003
DOI: 10.1179/030192303225004187
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nature and particle size distribution on granulation of iron ore mixtures used in a sinter strand

Abstract: ores and of an ore mixture. The ore mixture is used in Spain, and Drs Ferná ndez Pello, Mené ndez, and Muñ iz are with CENIM's pilot plant to manufacture a series of sinters, ACERALIA Corporació n Siderú rgica. Apartado 570, 33280 Gijó n, whose chemical compositions and quality indices are deterSpain. Manuscript

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
2
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 3 publications
1
34
2
3
Order By: Relevance
“…Some steel mills use this understanding in the design of their sinter ore blend. 7) In this study, it was observed that nucleus-forming particles were typically greater than 1 mm in size. Adhering particles were typically less than 0.5 mm in size, though occasionally up to 0.75 mm.…”
Section: Discussionmentioning
confidence: 91%
“…Some steel mills use this understanding in the design of their sinter ore blend. 7) In this study, it was observed that nucleus-forming particles were typically greater than 1 mm in size. Adhering particles were typically less than 0.5 mm in size, though occasionally up to 0.75 mm.…”
Section: Discussionmentioning
confidence: 91%
“…En la tabla I se puede apreciar cómo varían la composición de las fases y los índices de calidad del sinterizado en función de la Tmax alcanzada en el lecho [5] . Se observa que los mejores resultados se obtienen en el intervalo de 1.225-1.275°C, con un porcentaje máximo de ferritos, alto de hematita primaria, bajo de hematita secundaria, buena porosidad y buenos índices de calidad (FeO, RDI, RI y SI).…”
Section: Relación Entre El Frente De Llama Y La Estructura Del Sinterunclassified
“…Estas fases son: hematita no asimilada o residual, también denominada hematita primaria; hematita precipitada o hematita secundaria; magnetita; silicoferritos de calcio y aluminio (SFCA) y ganga formada, principalmente, por silicatos de calcio, hierro y magnesio [1][2][3][4][5] .…”
Section: Introduccionunclassified
“…Los gránulos formados se cargan sobre la parilla de la banda de sinterización, en donde la temperatura de los gránulos se eleva entre 1.250 y 1.350 °C para producir la fusión parcial y producir material semifundido, el cual, durante el enfriamiento posterior, cristaliza en varias fases minerales de distinta composición química y morfológica, principalmente, hematita, magnetita, ferritos y ganga formada en sus mayor parte por silicatos cálcicos [1][2][3] . La energía del proceso la suministra la combustión del coque.…”
Section: Introductionunclassified